Call auction, continuous trading and closing price formation. Issue 6 (3rd June 2021) - Li, Jiayi; Luo, Sumei; Zhou, Guangyou
Abstract : The Shanghai Stock Exchange changed its trading mechanism of the preceding three minutes to closing from continuous trading to call auction on August 20, 2018, while Shenzhen had already changed this in 2006. Taking all A-shared stocks' data from 2017 to 2019 as our sample, we construct difference-in-difference models and find significant trading volume shifts from closing call to preceding continuous trading. We also see a significant increase in volatility in call preceding continuous trading, but a significant decrease in closing price deviation in a closing call. Market efficiency is found to be improved by these changes, perhaps due to less liquidity noise in the closing price. Our conclusions remain robust in various robustness checks. It suggests that the introduction of closing call auction would reduce manipulation and liquidity noise in the closing price, thus improving market efficiency in China.